ANALISIS KEMISKINAN DI JAWA TENGAH - Dicky Wahyudi; Tri Wahyu Rejekingsih (Universitas Diponegoro, 2013)
Percentage of poor people in Indonesia are concentrated in Java Island by more than 50%. Central Java was the province of a percentage of the highest poverty rates in Java in recent years. Persistent higher average absolut poverty rate in Central Java at the level 20.02% that is including in Hard Core Poverty category (> 10%). Then almost of 50% regencies / cities in Central Java still has a absolut poverty rate > 20%. This study aims to analyze poverty and to know what variables has affected poverty rate in Central Java. The method of analysis used in this study are panel data regression with fixed effect model. This research’s model using dummy regions that function to discern the different character of poverty rate in each regencies / cities in Central Java, therefore the fixed effect model is also called least square dummy variable (LSDV).The results showed that health, education, government expenditure, unemployment has significant impact on poverty rate in Central Java. Meanwhile, economic growth has not significant on poverty rate. Increasing government expenditure especially in the functions of health, education, public utilities, and general social protection will impact the lower poverty rate. While the government health care for the poor is essential to increase their welfare. Education can dismiss a person from backwardness and poverty. Unemployment effected to lower welfare because the unemployed do not get revenue and closer to the poverty, therefore creating more job and employment opportunities vastly needed to reduce poverty.